YOUTUBE DAN PERKEMBANGAN ANAK BALITA - Ningsih, Gita Dwi; Yazim, Muhammad Anan; Ilmaliah, Fathina Fitriyia; Ustazah, Bungga (Universitas Teuku Umar, 2025)
This research aims to determine the influence of Youtube social media on the developmental aspects of children aged 2-4 years. This research method uses qualitative, with a literature review approach as a data collection technique. Technological developments mean that humans can access anything easily. In this current era, technology is rampant and humans can learn through technology, because technology is also a learning medium for searching for things. Youtube social media can be a learning medium for children under five, starting from language learning by getting examples from the content they watch. Youtube social media has two influences on children under five, which are positive and negative. Children basically see, hear, and model what they see and hear.